Strategies for Poly(3-hydroxybutyrate) Production Using a Cold-Shock Promoter in Escherichia coli - Boontip, Thanawat; Waditee-Sirisattha, Rungaroon; Honda, Kohsuke; Napathorn, Suchada Chanprateep (Frontiers in Bioengineering and Biotechnology, 2021)
The present study attempted to increase poly(3-hydroxybutyrate) (PHB) production by improving expression of PHB biosynthesis operon derived from Cupriavidus necator strain A-04 using various types of promoters. The intact PHB biosynthesis operon of C. necator A-04, an alkaline tolerant strain isolated in Thailand with a high degree of 16S rRNA sequence similarity with C. necator H16, was subcloned into pGEX-6P-1, pColdI, pColdTF, pBAD/Thio-TOPO, and pUC19 (native promoter) and transformed into Escherichia coli JM109. While the phaCA–04 gene was insoluble in most expression systems tested, it became soluble when it was expressed as a fusion protein with trigger factor (TF), a ribosome associated bacterial chaperone, under the control of a cold shock promoter. Careful optimization indicates that the cold-shock cspA promoter enhanced phaCA–04 protein expression and the chaperone function of TF play critical roles in increasing soluble phaCA–04 protein. Induction strategies and parameters in flask experiments were optimized to obtain high expression of soluble PhaCA–04 protein with high YP/S and PHB productivity. Soluble phaCA–04 was purified through immobilized metal affinity chromatography (IMAC). The results demonstrated that the soluble phaCA–04 from pColdTF-phaCABA–04 was expressed at a level of as high as 47.4 ± 2.4% of total protein and pColdTF-phaCABA–04 enhanced soluble protein formation to approximately 3.09−4.1 times higher than that from pColdI-phaCABA–04 by both conventional method and short induction method developed in this study. Cultivation in a 5-L fermenter led to PHB production of 89.8 ± 2.3% PHB content, a YP/S value of 0.38 g PHB/g glucose and a productivity of 0.43 g PHB/(L.h) using pColdTF-phaCABA–04. The PHB film exhibited high optical transparency and possessed Mw 5.79 × 105 Da, Mn 1.86 × 105 Da, and PDI 3.11 with normal melting temperature and mechanical properties.